2023
DOI: 10.31925/farmacia.2023.4.19
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Synergism Between Sildenafil and Metformin in an Animal Model of Diabetic Neuropathy Induced by Alloxan

CIPRIAN PUȘCAȘU

Abstract: Given the complex mechanism of diabetic neuropathy, evaluating the effect of drug combinations in this pathology is of an utmost importance. The aim of this study was to evaluate the synergism between sildenafil and metformin in an alloxan induced diabetic neuropathy mouse model. The pain latency times obtained for male mice in the cold and heat hypersensitivity tests, as well as the administered drug doses were processed and analysed in Python Programming Language by using the Multidimensional Synergy of Comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(72 reference statements)
0
0
0
Order By: Relevance
“…On the other hand, preclinical research showed that the cold hypersensitivity test revealed synergism between sildenafil and metformin, with sildenafil enhancing metformin’s potency and vice versa. This indicates a reduced required dose of each drug when administered together, compared to when they are administered alone, for reducing heat hyperalgesia in DN-induced mice [ 59 ]. Additionally, metformin has been found to possess neuroprotective properties that are beneficial in conditions involving neuropathic pain [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, preclinical research showed that the cold hypersensitivity test revealed synergism between sildenafil and metformin, with sildenafil enhancing metformin’s potency and vice versa. This indicates a reduced required dose of each drug when administered together, compared to when they are administered alone, for reducing heat hyperalgesia in DN-induced mice [ 59 ]. Additionally, metformin has been found to possess neuroprotective properties that are beneficial in conditions involving neuropathic pain [ 60 ].…”
Section: Discussionmentioning
confidence: 99%